2020
DOI: 10.1007/s41324-020-00372-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 induced lockdown on the changes of air quality and land surface temperature in Kolkata city, India

Abstract: The COVID-19 pandemic and related lockdown reduced the pollution level in the major megacities worldwide. The air pollution level of the city directly influences the air temperature and also land surface temperature (LST). In this paper, authors analyzed the impact of lockdown due to COVID-19 pandemic on the pollution level of the city and resulted LST. Single channel algorithm has been used to retrieve LST from Landsat Thematic Mapper satellite data. Pre-lockdown and post-lockdown satellite data has been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
1
8
0
1
Order By: Relevance
“…Similar results were found in ground-based air temperature measurements which were also largely negative with the exception Mumbai. Similar reductions in LST during the pandemic have been found in Kolkata ( Bera et al, 2020 ; Sahani et al, 2020 ) and the Dwarka river basin (West Bengal province, Mandal and Pal et al, 2020 ) where average Landsat-derived LST decreases of between 0.2 and 5 °C have been reported and which attributed to reduction in atmospheric pollutants and aerosols. In their analysis of Landsat LST over a number of large cities in India during the pandemic, Nanda et al (2021) also found most exhibited a decreases in LST except Kolkata which saw in increase in surface temperature.…”
Section: Discussionsupporting
confidence: 75%
“…Similar results were found in ground-based air temperature measurements which were also largely negative with the exception Mumbai. Similar reductions in LST during the pandemic have been found in Kolkata ( Bera et al, 2020 ; Sahani et al, 2020 ) and the Dwarka river basin (West Bengal province, Mandal and Pal et al, 2020 ) where average Landsat-derived LST decreases of between 0.2 and 5 °C have been reported and which attributed to reduction in atmospheric pollutants and aerosols. In their analysis of Landsat LST over a number of large cities in India during the pandemic, Nanda et al (2021) also found most exhibited a decreases in LST except Kolkata which saw in increase in surface temperature.…”
Section: Discussionsupporting
confidence: 75%
“…The negative nighttime LST anomalies during the lockdown weakened the UHI effect ( Founda et al, 2015 ; Gaffin et al, 2008 ; Sahani et al, 2020 ). This is justified by the larger reduction in LST (by about 1–2°C) that was found in the urban areas ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are signi cant impacts that has been observed in the major megacity of the world. For example, the lockdown due to COVID-19 pandemic in the cities caused the pollution level of the city signi cantly improved (Sahani et al, 2020). As shown in Table 4, 17.8% of the participants stated that they have full lockdown.…”
Section: Descriptive Analysis Of Climate Change Impacts On Cities Liveabilitymentioning
confidence: 98%